Endobronchial ultrasound for T4 staging in patients with resectable NSCLC - Kuijvenhoven, Jolanda C.; Livi, Vanina; Szlubowski, Artur; Ninaber, Maarten; Stöger, J. Lauran; Widya, Ralph. L.; Bonta, Peter. I.; Crombag, Laurence C.; Braun, Jerry; van Boven, Willem Jan; Trisolini, Rocco; Korevaar, Daniël A.; et al. (Lung cancer (Amsterdam, Netherlands), 2021)
•Lungtumors positioned adjacent to the central airways can be visualized by EBUS.•EBUS imaging can assess the presence or absence of mediastinal/vascular tumor invasion.•EBUS provides important additional staging information complementary to CT findings.•T4 assessment by EBUS cab be considered following an nodal examination. In lung cancer patients, accurate assessment of mediastinal and vascular tumor invasion (stage T4) is crucial for optimal treatment allocation and to prevent unnecessary thoracotomies. We assessed the diagnostic accuracy of linear endobronchial ultrasound (EBUS) for T4-status in patients with centrally located lung cancer. This is a retrospective study among consecutive patients who underwent EBUS for diagnosis and staging of lung cancer in four hospitals in The Netherlands (Amsterdam, Leiden), Italy (Bologna) and Poland (Zakopane) between 04–2012 and 04−2019. Patients were included if the primary tumor was detected by EBUS and subsequent surgical-pathological staging was performed, which served as the reference standard. T4-status was extracted from EBUS and pathology reports. Chest CT’s were re-reviewed for T4-status. 104 patients with lung cancer in whom EBUS detected the primary tumour, and who underwent subsequent surgical-pathological staging were included. 36 patients (35 %) had T4-status, based on vascular (n = 17), mediastinal (n = 15), both vascular and mediastinal (n = 3), or oesophageal invasion (n = 1). For EBUS, sensitivity, specificity, PPV and NPV for T4-status were (n = 104): 63.9 % (95 %CI 46.2–79.2 %), 92.6 % (83.7–97.6 %), 82.1 % (65.6–91.7 %), and 82.9 % (75.7–88.2 %), respectively. For chest CT (n = 72): 61.5 % (95 %CI 40.6–79.8 %), 37.0 % (23.2–52.5 %), 35.6 % (27.5–44.6 %), and 63.0 % (47.9–75.9 %), respectively. When combining CT and EBUS with concordant T4 status (n = 33): 90.9 % (95 %CI 58.7–99.8 %), 77.3 % (54.6–92.20 %), 66.7 % (47.5–81.6 %), and 94.4 % (721−99.1%), respectively. Both EBUS and CT alone are inaccurate for assessing T4-status as standalone test. However, combining a negative EBUS with a negative CT may rule out T4-status with high certainty.